We can also solve this question by method of separation of variables . We look for particular solution on the form -
"z(x,y)=f(x)g(y)"
"=(g\\dfrac{df}{dx})(f\\dfrac{dg}{dy})=xy\\implies" "fdf=xdx" "\\implies" "f={\\pm}\\sqrt{x^{2}+c_1}"
"gdg=ydy" "\\implies" "g={\\pm}\\sqrt{y^{2}+c_2}"
So the function of z will become as -
"z(x,y)=" "{\\pm}" "\\sqrt{x^{2}+c_1}\\sqrt{y^{2}+c_2}"
With condition z"(x,0)=x={\\pm}\\sqrt{(x^{2}+c_1)c_2}" "\\implies" "c_1=0;c_2=1;" sign of "x"
"z(x,y)=x\\sqrt{y^{2}+1}"
Solving with method of characteristics we get -
"=\\dfrac{dx}{q}=\\dfrac{dy}{p}=\\dfrac{dz}{2pq}=\\dfrac{dp}{y}=\\dfrac{dq}{x}=\\dfrac{dt}{1}"
"=x_0=s,y_0=0,z_0=s,p_0=1,q_0=0"
Solving the system leads to -
"x=Ae^{t}+Be^{-t}"
"y=Ce^{t}+De^{-t}"
"p=Ce^{2t}-De^{2t}"
"q=Ae^{2t}-Be^{2t}"
"z=ACe^{2t}-BDe^{2t}+E"
"=pq-xy=0" "\\implies" "AB+BC=0"
with boundary conditions ; "p_0=1; q_0=0"
A"+B=s;\\ C+D=0" ";AC-BD+E=s" ";C-D=1;A-B=0;AD+BC=0"
"A=B=E=\\dfrac{s}{2}" and "C=-D=\\dfrac{1}{2}\\implies" "x=hcosht"
"y=sin(ht)"
"z=\\dfrac{s}{2}(cosh(2t)+1)=scosh^{2}t"
"x^{2}-y^{2}s^{2}=s\\implies" "s^{2}=\\dfrac{x^{2}}{y^{2}+1}"
"z=\\dfrac{x^{2}}{s}" "=x^{2}(\\dfrac{+\\sqrt{y^{2}+1}}{x})"
"z=x\\sqrt{y^{2}+1}"
Comments
Leave a comment